EFEKTIVITAS AKUPRESUR DAN PUDING KELOR JAGUNG MANIS TERHADAP GEJALA PREMENSTRUAL SYNDROME (PMS) PADA REMAJA PUTRI DI PRODI KEBIDANAN KARAWANG - Trisnawati, Irna; Silawati, Vivi; Azzahroh, Putri; Antini, Ari (Universitas Jenderal Achmad Yani Yogyakarta, 2025)
Background: 90% of women who are of reproductive age, according to estimates worldwide experience premenstrual syndrome, which impacts mental well-being, quality of life, and academic achievement. If left untreated, it can lead to severe symptoms called Premenstrual Dysphoric Disorder (PMDD).Objective: To determine the effectiveness of acupressure and sweet corn moringa pudding on PMS in adolescent girls.Methods: A quasi-experimental study with a pre- and post-test a control group design. The sample consisted of 56 adolescents with PMS who were divided into case and control groups. The sample collection technique used a purposive sampling technique. The data were analyzed using descriptive statistics and inferential statistics, namely paired t-test and independent t-test to determine the differences in PMS scores between groups.Results: The average reduction in PMS scores was greater in the case group, at 14.39. There was a considerable difference in PMS scores before and after acupressure and sweetcorn moringa pudding in the case group (p<0.05), and there was a substantial difference in PMS scores between the case group and the control group after acupressure and sweetcorn moringa pudding (p<0.05)Conclusion: Acupressure and sweet corn moringa pudding can help reduce PMS in adolescents